Association of Benzodiazepine Receptor Agonist Use With Changes in Psoriasis Severity in Adult Population: A Population-Based Study - Pan, Ke-Ting; Li, I-Hsun; Kao, Hui-Han; Chen, Yi-Hsien; Zhong, Pei-Xun; Kao, Li-Ting (Frontiers in Pharmacology, 2021)
To date, it remains uncertain whether benzodiazepine receptor agonists (BZRAs) are aggravating factors even though these drugs can elevate the levels of biomarkers associated with the development of psoriasis. Therefore, this study aimed to investigate the association of BZRA use with changes in psoriasis severity. All data were sourced from the National Health Insurance system in Taiwan. We conducted a population-based retrospective cross-sectional study of 15,727 psoriasis patients who received BZRAs (BZRA users), and 18,856 psoriasis patients who did not receive BZRAs (nonusers). At least a 1-year washout period without any BZRA prescriptions was required. The main outcome was the change in psoriasis severity between before and after BZRA exposure. This study detected the exacerbation of psoriasis severity in mild psoriasis population by using a logistic model. Then, this study carried another logistic model among those patients who had severe psoriasis to calculate the odds ratios (ORs) for the improvement of the psoriasis severity. Among patients with mild psoriasis, BZRA users had a significantly higher probability of psoriasis severity exacerbation (IPTW-adjusted OR = 1.46). Mild psoriasis patients who received high and low doses of BZRAs had 1.70- and 1.39-fold higher probabilities of psoriasis severity exacerbation, respectively, than the non-users. Furthermore, in the severe psoriasis population, more low-dose BZRA users improved psoriasis severity than non-users. In conclusion, this study provided clinical evidence of the effects of BZRA use on patients with psoriasis severity. Among patients with mild psoriasis, high-dose BZRA users may be associated with the changes in psoriasis severity. However, low-dose BZRA exposure only slightly exacerbated disease severity among patients with mild psoriasis. Accordingly, clinicians should evaluate the risks and benefits of the BZRA usage.